Endoscopic duodenal mucosal resurfacing for nonalcoholic steatohepatitis (NASH): a pilot study - Alia Hadefi (Georg Thieme Verlag KG, 2021)
Background and study aims Nonalcoholic steatohepatitis (NASH) is a leading cause of chronic liver disease worldwide with limited treatment options. Duodenal mucosal resurfacing (DMR) has been associated with improvement in glycaemic parameters and liver function tests (LFTs) in type 2 diabetes. This study aimed to assess the effect of DMR in patients with NASH. Patients and methods This was a single-center, open-label pilot study. Patients with definite, biopsy-proven NASH (nonalcoholic fatty liver disease activity score [NAS] ≥ 4) underwent a single DMR procedure followed by a 2-week postprocedural diet, without lifestyle intervention. The primary outcome was either resolution of NASH with no worsening of fibrosis or improvement in fibrosis (≥ 1 stage) with no worsening of NASH at 12 months. Secondary outcomes were changes in key histological parameters of NASH, surrogate markers of fibrosis, LFTs, and metabolic factors at 12 months. Results From 2017 to 2019, 14 patients underwent successful DMR, of whom 11 were included in the analysis. After 12 months, no resolution of NASH was observed, while three patients (27 %) had marginal improvement in fibrosis with no worsening of NASH. Serious adverse events related to the procedure were reported in two patients out of 14 (14 %). Neither weight loss nor improvement in NAS score, or in the other secondary outcomes, were observed at 12 months. Conclusions In this small and heterogenous study population, we found that DMR, in the absence of lifestyle intervention, did not induce NASH resolution and marginally improved liver fibrosis at 12 months.